Uso de imagens aéreas de alta resolução espacial para a detecção e caracterização de processos erosivos - Weis, Maíra Guarlot (2020)
Space technologies have allowed productivity gains and an improvement in cost-benefit, being the case of most activities that depend on a spatio-temporal analysis of their occupation on the Earth's surface. Even with all the technological advances, georeferenced images still present positional uncertainties and, therefore, their quality must be evaluated in order to increase the accuracy of the generated products. In Brazil, this assessment can be made from the Cartographic Accuracy Standard for Digital Cartographic Products (PECPCD) defined by the Technical Specification for the Acquisition of Vector Geospatial Data (ET-ADGV) (DSG, 2011), being based on the Standard of Cartographic Accuracy (PEC) defined in Decree-Law no. 89,817 of 1984, which regulates the classification of products as to their accuracy. In this work, the objective was to use control points collected with a GNSS receiver to reduce the uncertainties / positional errors of georeferenced images in order to contribute to the search for functional and dynamic forms of management, control and environmental recovery. The study area is located in the northeastern region of the municipality of Rondonópolis - MT, with approximately 77 hectares. For the mapping of the area, aerial photographs of high spatial resolution were used, obtained by means of an RPA model DJI Phantom 4 Pro, and six control points were collected in the area using a GNSS Topcon Hiper V receiver. Data processing was performed using the Agisoft Metashape Professional software. As a final product, the Digital Terrain Model - MDT was obtained together with the level curves and, for comparative purposes, two processing reports were generated, one before the insertion of the support points and the other containing the points. The insertion of the control points significantly decreased the projection errors contained in the referenced images, whereas before the total error in the x, y and z axes was estimated at 8.507m and after the insertion the error became 0.191m.